Does neighbours' grass matter? Testing spatial dependent heterogeneity in technical efficiency of Italian hospitals. (November 2020) - Cavalieri, Marina; Di Caro, Paolo; Guccio, Calogero; Lisi, Domenico
Abstract: Testing for spatial dependent heterogeneity in hospital technical efficiency is crucial for separating spatial issues from the effects of regional institutional factors. We apply the Spatial Stochastic Frontier Analysis for studying the presence of spatial dependence by using novel data on Italian hospitals. This approach provides both a robust estimation of hospital technical efficiency and a careful assessment of spatial and regional issues. We find empirical support for the idea that regional and institutional factors are more important than neighbouring effects when looking at heterogeneity in hospital technical efficiency across Italy. The relevance of the regional organization of the Italian hospital system can justify our results. We also discuss the limitations of our analysis and provide sensitivity checks. Highlights: The presence of spatial dependence is tested on a large sample of Italian hospitals. Institutional factors are key factors for understanding hospital technical efficiency. Neighbouring effects are not relevant in hospital technical efficiency in Italy. The empirical findings are explained by the regional organization of the Italian NHS.